Remarkable improvement in microstructure and mechanical properties of cold sprayed Al deposits via impact forging post-spray treatment. (August 2022) - Ren, Yupeng; Haq Tariq, Naeem ul; Liu, Hanhui; Cui, Xinyu; Shen, Yanfang; Wang, Jiqiang; Xiong, Tianying
Abstract: A viable and novel approach was reported to significantly modify the microstructure and improve the mechanical properties of cold sprayed Al deposits. For this purpose, cold sprayed Al deposits were subjected to unidirectional impact forging in the temperature range of 250–300 °C. The evolution of microstructure and mechanical properties of the deposits were studied in detail. The results indicated that, hot-forging may significantly reduce the porosity in the deposits, and remarkably improve the Al/Al bonding due to enhanced inter-particle diffusion, dynamic recovery, and recrystallization mechanisms. Consequently, the ultimate tensile strength (UTS) and elongation in the Al deposits were remarkably enhanced from 26.2 ± 2.4–95.7 ± 1.7 MPa and 0.8 ± 0.05–36.3 ± 2.6%, respectively. Graphical Abstract: ga1 Highlights: Hot-forging is introduced for CSed Al deposit as an effective post-spray treatment. Hot-forging resulted in efficient healing of voids and particle-particle boundaries. Mechanical properties of CSed Al deposit was dramatically improved via hot-forging.